Seasonal variation of antibiotics in surface water of Pudong New Area of Shanghai, China and the occurrence in typical wastewater sources. (January 2020) - Pan, Chenyuan; Bao, Yangyang; Xu, Bentuo
Abstract: The occurrence of 26 antibiotics from three groups of Sulfonamides, Quinolones and Macrolides were investigated in the surface water of Pudong New Area, Shanghai in March (dry season) and June (wet season). As a result, the detection rates of the three groups were 20%, 81% and 56% (n = 10) with the concentration range of not detected–9.73 ng L −1, 30–344 ng L −1, and 14–107 ng L −1, respectively. Comparably, during wet season, the detection rates were 20%, 56% and 25% with the range of ND–14 ng L −1, 32–92 ng L −1, and ND–22 ng L −1, respectively. This indicates higher concentrations in dry season than that in wet season, which was attributed to the water dilution and weaker self-purification of the river during dry season. In addition, significant correlations were observed between SMA and most of Quinolones during dry season, and Quinolones and Macrolides during wet season, due to the similar sources. Considering for the typical wastewater sources in the investigated area, Quinolones were identified to be the most significant group in the aquiculture water. Furthermore, pharmaceutical manufacturing factory (PMF) and sewage treatment plant (STP) should be the serious point source pollution as the concentration in their effluents could range from ng L −1 to mg L −1 . The occurrence and fate of antibiotics in the aquatic system of Pudong New Area need to be paid more attention to prevent the potential risk for human beings in the future study. Graphical abstract: Image 1 Highlights: 26 antibiotics were detected in surface water from Huangpu river system. Most of antibiotic concentration were higher in dry season than that in wet season. The pig farm was the potential pollution source of SMA in this area. Risk quotient values of ciprofloxacin were over 1.0 in all sampling sites.